819 Targeting vasoactive intestinal peptide receptor signaling: a novel approach to enhance anti-tumor response in pancreatic ductal adenocarcinoma. (9th November 2020) - Ravindranathan, Sruthi; Tenzin, Passang; Chandrasekaran, Sanjay; Ware, Brandon; Zaidi, Mohammad; Wang, Shuhua; Dhamsania, Rohan; Zhu, Jingru; Thomas, Susan; Majumdar, Anish; Lesinski, Gregory; El-rayes, Bassel; et al.
Abstract : Background: Pancreatic ductal adenocarcinoma (PDAC), the fourth leading cause of cancer related death in the U.S, has a 5-year survival rate of only 10%. 1 The paucity of T cells in the immune privileged tumor microenvironment (TME) is a major limitation in developing an effective immunotherapy against PDAC. 2 The cancer genome atlas (TCGA) shows that human PDAC tumors express high levels of vasoactive intestinal peptide (VIP), an immunosuppressive neuropeptide (figure 1 A), that inhibits effector T cell responses. 3 4 We hypothesized that paracrine secretion of VIP in the TME is a targetable mediator of immune paralysis in PDAC, and that pharmacological inhibition of VIP receptor signaling could enhance anti-tumor responses in PDAC. Methods: VIP levels in plasma or cell culture supernatant was determined via VIP-specific enzyme immunoassay. Luciferase transfected KPC (KPC.luc) cells were injected subcutaneously or orthotopically into the pancreas of C57BL/6, CD4KO, or CD8KO mice from Jackson Laboratories. C57BL/6 mice T cell subsets in were depleted post tumor implantation with anti-CD4 and/or anti-CD8 antibodies. Tumor-bearing mice were treated daily with ANT008, a novel VIP receptor antagonist peptide, and/or anti-PD1 monoclonal antibody (MoAb) for 10 days, starting 7-10 days after implantation. T cells isolated from peripheral blood of PDAC patients were expanded 9 days ex vivo in anti-CD3 MoAb coated plates with 30U/ml IL-2 and either control peptide (scrambled VIP sequence) or ANT008. Survival by VIP and VIP receptor expression from the TCGA was clinically correlated. Results: Increased human and mouse PDAC expression correlates with elevated blood levels (figure 1 ). While the PDAC cancer cell lines express VIP receptors, ANT008 does not have direct cytotoxic effect on cell growth in vitro (figure 2 ). However, in orthotopic KPC model, treatment with ANT008 & anti-PD-1 significantly decreased tumor growth rate and burden (figure 3 ) while increasing the intratumoral levels of CD4 and CD8 proliferating T cells (figure 4 ) via a T cell dependent mechanism (figure 5 ). Additionally, in ex vivo cultures of T cells isolated from PDAC patients, ANT008 improved the effector properties of T cells via decreasing expression levels of co-inhibitory molecules and decreasing frequency of regulatory T cells (figure 6 ). Clinically, VIPR1 receptor expression, but not VIP, provides a survival benefit (figure 7 ). Conclusions: VIP is a targetable mechanism of immune escape in PDAC. Inhibiting VIP receptor signaling improves effector properties of T cells and synergistically improves the anti-tumor response to checkpoint inhibitors in mouse PDAC models. References: Siegel RL, Miller KD, Jemal A. Cancer statistics, 2020. CA Cancer J Clin 2020;70(1):7-30. Sahin IH, et al. Immunotherapy in pancreatic ductal adenocarcinoma: an emerging entity? Ann Oncol 2017;28(12):2950-2961. Gonzalez-Rey E, Anderson P, Delgado M. Emerging roles of vasoactive intestinal peptide: a new approach for autoimmune therapy. Ann Rheum Dis 2007;66(Suppl 3):iii70-6. Anderson P, Gonzalez-Rey E. Vasoactive intestinal peptide induces cell cycle arrest and regulatory functions in human T cells at multiple levels. Mol Cell Biol 2010;30(10):2537-51.